2018
DOI: 10.31234/osf.io/tgua4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gesture-Speech Physics: The Biomechanical Basis for the Emergence of Gesture-Speech Synchrony

Abstract: Hand gestures and speech move in a common rhythm, as exemplified by the synchrony between prosodic contrasts in gesture movement (e.g., peak velocity; maximum effort) and speech (e.g., peaks in fundamental frequency; F0). This joined rhythmic activity is hypothesized to have a variable set of functions, ranging from self-serving cognitive benefits for the gesturer, to communicational advantages that support listeners’ understanding. However, gesture-speech synchrony has been invariably understood as a “neural-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Such peaks in phonation were observed at the moment at which posturally destabilizing forces of the arm movements were highest and at which the body counteracted such forces by tensioning of the muscles in anticipatory fashion. Indeed, we found that anticipatory postural adjustments played a role in movementphonation resonance, as peaks in phonation were more pronounced when participants were standing versus sitting (Pouw, Harrison, et al, 2018b). Previous research has found that, when standing, the forces produced during upper-limb movements are more destabilizing; as a result, thus the body must be more forcefully tensioned via the myofascial-skeletal network so as to keep postural integrity (Cordo & Nashner, 1982).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Such peaks in phonation were observed at the moment at which posturally destabilizing forces of the arm movements were highest and at which the body counteracted such forces by tensioning of the muscles in anticipatory fashion. Indeed, we found that anticipatory postural adjustments played a role in movementphonation resonance, as peaks in phonation were more pronounced when participants were standing versus sitting (Pouw, Harrison, et al, 2018b). Previous research has found that, when standing, the forces produced during upper-limb movements are more destabilizing; as a result, thus the body must be more forcefully tensioned via the myofascial-skeletal network so as to keep postural integrity (Cordo & Nashner, 1982).…”
Section: Introductionmentioning
confidence: 63%
“…In the current paper, we will explore the possibility that visual information from gesture is but one of its (communicatively meaningful) products. Recently, we have found that upper-limb movements with relatively high physical impetus produce prominent but non-intentional changes in voice quality (Pouw, Harrison, & Dixon, 2018b). Specifically, we found peaks in the fundamental frequency (F0) and the amplitude envelope (energy in the signal) of continuous phonation of the vowel /a:/ when participants made high-impact movements that recruited the entire arm (see Figure 1) but not when producing low-4 impact wrist movements or when standing still.…”
Section: Introductionmentioning
confidence: 99%
“…To provide a mechanism for self-entrainment, Pouw, Harrison, & Dixon (2018) found that when gestures have higher physical impetus on the body, peaks in the amplitude envelope and the fundamental frequency of phonation occur that increase over time. Such peaks are directly related to prosodic dimensions of speech and have been used as such in the study of the gesture and speech prosody correlation (for a review see Wagner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to iconic gestures, beat gestures are not related to the spoken message on a semantic level, but only on a temporal level: their apex is aligned to vowel onset in lexically stressed syllables carrying prosodic emphasis 20,21,34,54 . Neurobiological studies suggest that listeners may tune oscillatory activity in the alpha and theta bands upon observing the initiation of a beat gesture Bosker & Peeters 6 to anticipate processing an assumedly important upcoming word 44 .…”
Section: Introductionmentioning
confidence: 96%
“…Bosker & Peeters 5 [19][20][21] . We manually point at things to guide the attention of our addressee to relevant aspects of our immediate environment [22][23][24][25] , enrich our speech with iconic gestures that in handshape and movement resemble what we are talking about [26][27][28] , and produce simple flicks of the hand aligned to the acoustic prominence of our spoken utterance to highlight relevant points in speech [29][30][31][32][33][34] . Over the past decades, it has become clear that such co-speech manual gestures are semantically aligned and temporally synchronized with the speech we produce 35-40 . It is an open question, however, whether the temporal synchrony between these hand gestures and the speech signal can actually influence which speech sounds we hear.…”
Section: Introductionmentioning
confidence: 99%